"more than a little strange": Imagination and Ecology in Jayber Crow - Lambert, Christina J. (Christianity & literature, 2025)
In view of Wendell Berry's engagement with marriage as a metaphor for our relationship with the land, this paper considers how Jayber Crow's "strange marriage" draws attention to the imagination's role in relational and ecological healing. Berry's novel, Jayber Crow, demonstrates the transformation of Jayber's imagination from a self-fulfilling, objectifying gaze to a vision that fosters faithfulness in the world, resulting in his imagined marriage vow. Jayber's transformed imagination models the fruits of a whole imagination that encompasses grief, imagines a creational covenant, and, as the Mad Farmer says, practices resurrection.